Interdepartmental Collaboration between Food and Beverage Product and Service in Breakfast Operations at Platinum Adisucipto Hotel Yogyakarta - Kurniawati, Neni (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2025)
The working relationship between the Food and Beverage Product (kitchen) and the Food and Beverage Service(restaurant) is a crucial form of collaboration in hotel operations, particularly during breakfast service. This study aims to analyse the forms of interdepartmental collaboration, identify supporting and inhibiting factors, and examine the role of each staff member in ensuring the smooth operation of breakfast at Platinum Adisucipto Hotel Yogyakarta. A descriptive qualitative method was employed through in-depth interviews with the Food and Beverage Manager, Executive Chef, Cook, and Waiter/Waitress, complemented by direct observation during breakfast operations. The findings reveal that the success of breakfast service is strongly influenced by effective coordination between Food and Beverage Product and Food and Beverage Service. The inhibiting factors identified include miscommunication and human error, while the supporting factors consist of effective communication and teamwork. Each staff member plays a significant role: the Food and Beverage Manager acts as a strategic coordinator and communication facilitator, the Executive Chef functions as a field supervisor and technical decision-maker, the Cook serves as both a production executor and team solidarity builder, while Waiters/Waitresses are the frontline staff bridging the interaction between guests and the kitchen. The study concludes that a harmonious and synergistic working relationship between Food and Beverage Product and Food and Beverage Service is the key to successful breakfast operations. Strengthening communication systems, work discipline, and teamwork culture is therefore essential to minimise operational barriers and enhance the quality of hotel service delivery.